On a Fractional Nonlinear Hyperbolic Equation Arising from Relative Theory - Zujin Zhang; Xiaofeng Wang; Zheng-an Yao (Abstract and Applied Analysis)
We obtain the existence of a weak solution to a fractional nonlinear hyperbolic equation arising from relative theory by the Galerkin method. Its uniqueness is also discussed. Furthermore, we show the regularity of the obtained solution. In our proof, we use harmonic analysis techniques and compactness arguments.